Ibn Taymiyyah on reason and revelation : a study of Dar' ta'arud al-'aql wa-l-naql - El-Tobgui, Carl Sharif, 1974- (Islamic philosophy, theology and science, 2020)
"In Ibn Taymiyya on Reason and Revelation, Carl Sharif El-Tobgui offers the first comprehensive study of Ibn Taymiyya's ten-volume magnum opus, Dar' ta'arud al-'aql wa-l-naql. In his colossal riposte to the Muslim philosophers and rationalist theologians, the towering Ḥanbalǐ polymath rejects the call to prioritize reason over revelation in cases of alleged conflict, interrogating instead the very conception of rationality that classical Muslims had inherited from the Greeks. In its place, he endeavors to articulate a reconstituted "pure reason" both truly universal and in full harmony with authentic revelation. Based on a line-by-line reading of the entire Dar' ta'arud, El-Tobgui's study carefully elucidates the "philosophy of Ibn Taymiyya" as it emerges from the multifaceted ontological, epistemological, and linguistic reforms Ibn Taymiyya carries out"--